Frequency control of microgrid system based renewable generation using fractional PID controller - Regad Mohamed; M. Helaimi; Rachid Taleb; Hossam A. Gabbar; Ahmed M. Othman (Institute of Advanced Engineering and Science, 2020)
This paper addresses a control frequency scheme of the microgrid system using a fractional order PID controller. The proposed Microgrid system is consisted of a photovoltaic system, wind turbine generator, diesel engine generator, fuel cell, and different storage systems like battery energy storage systems, and flywheel energy storage systems. The principal objective of the present paper is to limit the frequency and power deviations by the application of the proposed controller which has five parameters to be determined through optimization techniques. Krill Herd algorithm is used for determining the optimum fractional order PID controller parameters using the integral of squared error. A comparison between the genetic algorithm and krill herd is done, and the obtained simulation results presents that the investigated controller-based Krill Herd outperforms the Genetic Algorithm in terms of fewer fluctuations in power and frequency deviation.